2011
DOI: 10.1176/appi.ajp.2010.10050748
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging Dopamine Transmission in Cocaine Dependence: Link Between Neurochemistry and Response to Treatment

Abstract: Previous research has shown that dopamine signaling in the limbic striatum is crucial for selecting adaptive, motivated behavior, and that disrupted dopamine transmission is associated with impulsive and maladaptive behavior. In humans, Positron Emission Tomography (PET) imaging studies have shown that cocaine dependence is associated with the dysregulation of striatal dopamine signaling, which is associated with cocaine seeking behavior. The goal of the present study was to investigate whether this associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
176
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 40 publications
17
176
2
Order By: Relevance
“…A deficit in striatal D2/D3 dopamine receptor binding is a common feature across substance use disorders (Bonci et al, 2013;Broft and Martinez, 2012). In stimulant dependence, this deficit is linked to treatment success rates (Martinez et al, 2011;Wang et al, 2012) and measures of impulsivity (Lee et al, 2009) and decision making (Ballard et al, 2015). Although these observations suggest that augmenting signaling at D2/D3 receptors may be an effective therapeutic target in substance use disorders, dopamine agonist therapy has shown limited success in improving treatment outcomes for stimulant dependence (Ling et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficit in striatal D2/D3 dopamine receptor binding is a common feature across substance use disorders (Bonci et al, 2013;Broft and Martinez, 2012). In stimulant dependence, this deficit is linked to treatment success rates (Martinez et al, 2011;Wang et al, 2012) and measures of impulsivity (Lee et al, 2009) and decision making (Ballard et al, 2015). Although these observations suggest that augmenting signaling at D2/D3 receptors may be an effective therapeutic target in substance use disorders, dopamine agonist therapy has shown limited success in improving treatment outcomes for stimulant dependence (Ling et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Extrastriatal VOIs for the hippocampus, amygdala, and thalamus were defined using the FSL software package and a whole striatum VOI was created by combining VOIs of the caudate, putamen, and nucleus accumbens. The functional subdivisions of the striatum (Martinez et al, 2011) and midbrain (Zald et al, 2010) were defined using published guidelines. The cerebellum was selected as an appropriate reference region (Hall et al, 1994;Ishibashi et al, 2013).…”
Section: Mri Scanning and Voismentioning
confidence: 99%
“…On the other hand, recently (Rominger et al, 2012) striatal DRD2/3 binding has been reported to increase significantly by 29% between the first day and 1 year of abstinence. Furthermore, it is interesting to note that in a recent [ 11 C]raclopride study by Martinez et al (2011), in cocaine addiction the patients who responded to contingency management treatment and thus remained abstinent did not differ from healthy controls in DRD2/3 levels measured pre-treatment. Similar results in methamphetamine-dependent patients have been reported by Wang et al (2012).…”
Section: D3 Receptors In Alcoholismmentioning
confidence: 97%
“…Therefore, a more detailed understanding of the (neural) mechanisms underlying the effects of impulsivity on treatment outcomes is needed, as this may lead to novel interventions aimed at minimizing these negative effects and may facilitate treatment responding in these subjects. One neural mechanism potentially linking impulsivity with poor treatment outcomes is a motivational deficit associated with dopamine dysfunction: pronounced disruptions in dopamine functioning associated with impulsivity may produce difficulties in attributing salience to novel reward-indicating stimuli (Beck et al, 2009;Martinez et al, 2011) and affect the ability of the individual to successfully modify behavior in the face of enriched rewarding contingencies (Goto & Grace, 2008). Speculatively, pharmacological interventions aimed at restoring dopamine functioning might facilitate CM-responding in these individuals by targeting neurobiological bottom-up processes associated with reward processing and salience attribution .…”
Section: Treatment Modification For High-impulsive Substance Abusersmentioning
confidence: 99%